Growth of "moth‐eye" ZnO nanostructures on Si(111), c‐Al2O3, ZnO and steel substrates by pulsed laser deposition. Issue 10 (6th August 2013) - Sandana, Vinod E.; Rogers, David J.; Teherani, Ferechteh Hosseini; Bove, Philippe; Molinari, Michael; Troyon, Michel; Largeteau, Alain; Demazeau, Gérard; Scott, Colin; Orsal, Gaelle; Drouhin, Henri‐Jean; Ougazzaden, Abdallah; et al.
Abstract Self‐forming, vertically‐aligned, arrays of black‐body‐like ZnO moth‐eye nanostructures were grown on Si(111), c‐Al2O3, ZnO and high manganese austenitic steel substrates using Pulsed Laser Deposition. X‐ray diffraction (XRD) revealed the nanostructures to be well‐crystallised wurtzite ZnO with strong preferential c‐axis crystallographic orientation along the growth direction for all the substrates. Cathodoluminescence (CL) studies revealed emission characteristic of the ZnO near band edge for all substrates. Such moth‐eye nanostructures have a graded effective refractive index and exhibit black‐body characteristics. Coatings with these features may offer improvements in photovoltaic and LED performance. Moreover, since ZnO nanostructures can be grown readily on a wide range of substrates it is suggested that such an approach could facilitate growth of GaN‐based devices on mismatched and/or technologically important substrates, which may have been inaccessible till present. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)